Characterization, cellular uptake in Caco-2 cells and physiologically based pharmacokinetic modeling of baicalin-loaded solid lipid nanoparticles - Hussein O. Ammar; Rehab N. Shamma; Carol Yousry; Rasha S. Elbatanony; Basma Khater; Amira M. Ghoneim (SpringerOpen, 2023)
Abstract Background Baicalin is a natural compound having intriguing and useful pharmacological properties that may be used alone or in conjunction with other treatments in a variety of therapeutic areas. However, the drug has low aqueous solubility and poor absorption. The aim of this research was to optimize the bioavailability of baicalin through incorporation into solid lipid nanoparticles. Results The particle size of the prepared baicalin-loaded solid lipid nanoparticles ranged between 248.2 ± 1.72 nm and 291.9 ± 30.9 nm. The speed, duration of homogenization and the content of both the surfactant and soy lecithin affected the particle size and the entrapment efficiency. The optimized formula showed superiority in drug release over the drug suspension, with biphasic release profile. Cell culture results showed good accumulation of the drug into the Caco-2 cells that increases over time in the case of the optimized formula. Physiologically based pharmacokinetic (PBPK) modeling simulated enhanced bioavailability of the optimized formula, compared to the drug suspension. Conclusion Solid lipid nanoparticles have demonstrated potential as cancer therapy nanocarriers. Reduced toxicity, improved drug absorption and flexibility in combining hydrophilic and lipophilic medications are all significant advantages of this system. The PBPK simulation suggested the safety of the optimized BA-SLNs in cancer patients and in geriatric populations.